Advertisements
Advertisements
Question
Solution 1
\[\text{We have}, \]
\[I = \int\frac{e^x \left( 1 - x \right)^2}{\left( 1 + x^2 \right)^2} \text{ dx }\]
\[ = \int\frac{e^x \left( 1 + x^2 - 2x \right)}{\left( 1 + x^2 \right)^2} \text{ dx }\]
\[ = \int e^x \left[ \frac{\left( 1 + x^2 \right)}{\left( 1 + x^2 \right)^2} - \frac{2x}{\left( 1 + x^2 \right)^2} \right] \text{ dx }\]
\[ = \int e^x \left( \frac{1}{1 + x^2} - \frac{2x}{\left( 1 + x^2 \right)^2} \right) \text{ dx }\]
\[ = \frac{e^x}{1 + x^2} + C.......................[ ∵ \int e^x { f ( x ) + f' ( x ) } \text{ dx }= e^x f( x ) + C\]` \text{ Where} ,ƒ (x } = 1/{1+2} ⇒ ƒ ^' (x ) = - {2x}/ (1+ x^2)^2 ]`
Solution 2
\[\text{We have}, \]
\[I = \int\frac{e^x \left( 1 - x \right)^2}{\left( 1 + x^2 \right)^2} dx\]
\[ = \int\frac{e^x \left( 1 + x^2 - 2x \right)}{\left( 1 + x^2 \right)^2} dx\]
\[ = \int e^x \left[ \frac{\left( 1 + x^2 \right)}{\left( 1 + x^2 \right)^2} - \frac{2x}{\left( 1 + x^2 \right)^2} \right] dx\]
\[ = \int e^x \left( \frac{1}{1 + x^2} - \frac{2x}{\left( 1 + x^2 \right)^2} \right) dx\]
\[ = \frac{e^x}{1 + x^2} + C \left[ \because \int e^x \left\{ f\left( x \right) + f'left( x \right) \right\} dx = e^x f\left( x \right) + C\]
APPEARS IN
RELATED QUESTIONS
Write a value of
If \[\int\frac{1}{5 + 4 \sin x} dx = A \tan^{- 1} \left( B \tan\frac{x}{2} + \frac{4}{3} \right) + C,\] then
\[\int\frac{x^3}{\sqrt{1 + x^2}}dx = a \left( 1 + x^2 \right)^\frac{3}{2} + b\sqrt{1 + x^2} + C\], then